Description of Synonyms in Linguodidactics: Integrative Approach (based on the Synonymous Row of Verbs with a Common Meaning ‘do nothing’) - E. I. Zinovieva; N. Y. Vu (Научный диалог)
The article is devoted to the description of a synonymous series of Russian verbs with a dominant idle against the background of the Vietnamese language for further presentation of Russian units in a Vietnamese audience. The approaches to the study of synonymous units traditionally highlighted in Russian linguistics are considered. The relevance of an integrative approach to the analysis of synonyms for linguodidactic purposes is substantiated. The novelty of the study is that such a comprehensive approach allows us to analyze synonyms at the level of the language system, discourse and language consciousness of native speakers. The relevance of the study is due to the fact that the synonymous row under study is included in the lexico-semantic group of behavior verbs, nuclear for the Russian language, as well as the lack of training dictionaries of Russian synonyms for foreign students. The authors determine the structure of the studied synonymic row in the Russian language, analyze the semantics, typical situations of use, the stylistic classification of units according to the components that make up the synonymic series. Particular attention is paid to data from a survey of native Russian speakers. A comparative analysis of Russian synonyms and their translation equivalents in the Vietnamese language is presented. Relevant parameters of the characteristics of the members of the synonymous row are identified to optimize the work with these units in the Vietnamese audience. Linguistic and methodological recommendations on the presentation of Russian synonyms in a Vietnamese audience are offered.